Evaluation of a carbon 13 breath test for the diagnosis of Helicobacter pylori - Bernui Vigo, Grazia María (2022)
Objective: To evaluate a Chinese-made carbon-13 breath test as a non-invasive diagnostic method for Hp infection in the Peruvian population through the determination of sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio, and diagnostic utility. Materials and methods: A cross-sectional and descriptive study was carried out on a secondary database of the Gastroenterology Service of the Cayetano Heredia Hospital and Cayetano Heredia Clinic from November 2017 to August 2018. Patients over 18 years of age who underwent endoscopy were included upper digestive. Results: A sensitivity of 90.3% (95% CI 0.81-0.96), a specificity of 82.5% (95% CI 0.67-0.93), a positive predictive value was found and negative of 90.3% and 82.5%, and positive and negative likelihood ratio of 5.16 and 0.12, respectively. The area under the ROC curve was 0.88 (95% CI: 0.80-0.96). Conclusions: The carbon 13 breath test is a non-invasive and simple test that provides results quickly. However, it is not possible to recommend the routine use of this test due to the discrepancy between the international and local results obtained. Studies with larger sam d protocols and different manufacturers are suggested to evaluate their performance and characteristics.